STUDY OF THE PIEZOMETRIC SURFACE AND HYDROCOMPACTION AT CONFINED AQUIFER CAUSED THE LAND SUBSIDENCE IN SEMARANG - Fahrudin Fahrudin; Najib Najib (TEKNIK, 2011)
Semarang city has experienced of the land subsidence that be caused by intake groundwater in confined aquiferabundant. The land subsidence happened during range of time 20 years, it’s critical boundary so that result theenvironmental damage. Hence needed a study of cause of the land subsidence. This study aim to know theposition of piezometric surface and also explain the mechanism hydrogeology when happened the landsubsidence. The study of spreading aquifer has been done by the analysis of secondary data which is in the formof drilling log data, piezometric surface and soil mechanics test obtained from PLG (Environmental Center ofGeology) Bandung. Later then, between the land subsidence and piezometric surface be overlay becamezonation. From the data made a analysis of cause of the land subsidence. This aquifer has the land subsidence.The land subsidence explainable with the experienced phenomenon fact for example degradation of piezometricsurface at confined aquifer and process of hydrocompaction. That process influenced by two factors that areassess the pore number (e) and specific gravity (Gs). The degradation of piezometric surface formed the trapezeof water table until 20 m from sea level with the mean 0.7 - 1.1 m/year. Hydrocompaction cause the degradationof number of mean pore 0.145 - 0.5 and specific gravity 0.009 - 0.073 . The degradation of piezometric surfaceand process the hydrocompaction cause the fast of land subsidence around 0.5 - 1.75 cm/year.